Impact of myofascial release therapy combined with isokinetic training on pain, function, and radiological outcomes in collegiate basketball players with subacromial impingement syndrome: a prospective randomized controlled trial - Nambi, G.; Alghadier, M.; Hegazy, M. M. A.; George, J. S.; Alomari, A. K.; Aldhafian, O. R.; Albarakati, A. J. A.; Mohamed, S. H. P.; Albalawi, H. F.; Eldesoky, M. T. M.; Abutaleb, E. E. M.; Zahran, S. S. (BMC Sports Science, Medicine and Rehabilitation, 2026)
Background Subacromial impingement syndrome (SIS) is a common condition in overhead athletes, associated with pain, impaired function, and altered shoulder mechanics. Conventional physiotherapy may not fully address underlying myofascial restrictions and neuromuscular deficits. Myofascial Release Therapy (MFR) and Isokinetic Training (IT) are promising interventions; however, their combined effects remain underexplored.